# How do you solve 4( s+ 8) - 3s = - 2?

Sep 6, 2017

$s = - 34$

#### Explanation:

$\setminus \textcolor{s t e e l b l u e}{4 \left(s + 8\right)} - 3 s = - 2$
$\setminus \textcolor{s t e e l b l u e}{4 \left(s\right) + 4 \left(8\right)} - 3 s = - 2$ Distributive property.
$\setminus \textcolor{s t e e l b l u e}{4 s + 32} - 3 s = - 2$ Simplify, then combine like terms.

$\setminus \textcolor{\in \mathrm{di} a n red}{4 s} \setminus \textcolor{s e a g r e e n}{+ 32} \setminus \textcolor{\in \mathrm{di} a n red}{- 3 s} = \setminus \textcolor{s e a g r e e n}{- 2}$ Identify like terms. Start with the coefficient variable terms.
$\setminus \textcolor{\in \mathrm{di} a n red}{4 s - 3 s} \setminus \textcolor{s e a g r e e n}{+ 32} = \setminus \textcolor{s e a g r e e n}{- 2}$ Combine previously mentioned terms.
$\setminus \textcolor{\in \mathrm{di} a n red}{s} \setminus \textcolor{s e a g r e e n}{+ 32} = \setminus \textcolor{s e a g r e e n}{- 2}$ Simplify, then do the same for the non-variable terms.

$s = \setminus \textcolor{s e a g r e e n}{- 2 - 32}$ Move all non-variable terms to the right.
$s = \setminus \textcolor{s e a g r e e n}{- 34}$ Combine those terms. Now you have your answer:

$s = - 34$

Sep 6, 2017

$\implies s = - 34$

#### Explanation:

$4 \left(s + 8\right) - 3 s = - 2$
$\implies 4 s + 32 - 3 s = - 2$
$\implies s + 32 = - 2$

Let's add $- 32$ to both side:
$s = - 2 - 32$
$\implies s = - 34$